EQUIVALENT REPRESENTATIONS OF HIDDEN MARKOV MODELS - SETIAWATY, B. (School of Data Science, Mathematics and Informatics, IPB University, 2003)
In this article, we classify the class of hidden Markov models through the laws of the observation processes, since the Markov chains are not observable. Here, we also present some properties regarding this classiﬁcation.